Automated High-Throughput Capillary Circular Dichroism and Intrinsic Fluorescence Spectroscopy for Rapid Determination of Protein Structure - Moore-Kelly, Charles (Anal Chem, 2019)
[Image: see text] Assessing the physical stability of proteins is one of the most important challenges in the development, manufacture, and formulation of biotherapeutics. Here, we describe a method for combining and automating circular dichroism and intrinsic protein fluorescence spectroscopy. By robotically injecting samples from a 96-well plate into an optically compliant capillary flow cell, complementary information about the secondary and tertiary structural state of a protein can be collected in an unattended manner from considerably reduced volumes of sample compared to conventional techniques. We demonstrate the accuracy and reproducibility of this method. Furthermore, we show how structural screening can be used to monitor unfolding of proteins in two case studies using (i) a chaotropic denaturant (urea) and (ii) low-pH buffers used for monoclonal antibody (mAb) purification during Protein A chromatography.